Literature Review: The Effect of Ajwa Date Fruit Consumption on Fasting Blood Sugar Levels in Perimenopausal Women - Hariandini, Elsa Amalia; Andi Mappaware, Nasrudin; Nawir, Nasarudin; Arfah, Arni Isnaini; Royani, Ida; Zulfahmida, Zulfahmida (Newinera Publisher, 2024)
The active substances contained in date extract such as flavonoids, steroids, phenols and saponins have an anti-diabetic function which is useful in controlling glycemic and fat in diabetes patients. Perimenopause is a poorly defined period of time that surrounds the final years of a woman's reproductive life, usually between the ages of 30 and 40. Insulin affects many hormones, including sex hormones (estrogen, progesterone, and testosterone). This hormonal imbalance can disrupt the balance of other hormones. In the basic principles of bioethics there are four aspects, namely beneficence, non-maleficence, autonomy and justice. Maqashid Al Shariat contains 5 values, namely Hifz ad din, hifz an nafs, hifz al maal, hifz al nasl, and hifz al aql. In the perspective of Islamic jurisprudence, it consists of five rules, namely Al Ageu bi Maqashida, La dharara wa laa dirara,, Al masyaqqah tajlibut, Al yaqinu la yuzalu bi syaq, and Al adatu muhakkamah. A 46 year old woman G1P1A0 Gravid 34 weeks with a history of regular menstruation every month. Blood pressure 110/80 mmHg with BMI 30.24 (Obes 2). The results of the fasting blood sugar examination were found to be 130 mg/dl. The diagnosis in this patient is diabetes mellitus. The treatment given to this patient is a regulated eating pattern and implementation of a diet pattern. In the bioethical perspective, it fulfills the non-maleficence aspect, the principles of fiqh are Al iau bi maqashida, La dharara wa laa dirara, and Al adatu muhakkamah.